Relación entre procrastinación y estrés académico en los estudiantes de bachillerato de la Unidad Educativa Jaime Roldós Aguilera del cantón Montalvo, Provincia de Los Ríos - Guizado Conde, Ambar Lizbeth (2025)
Academic procrastination is a specific type of procrastination that occurs when students postpone or delay tasks related to their studies, such as papers, projects, exams or readings. Therefore, this study seeks to determine the relationship between procrastination and academic stress in high school students of the Jaime Roldós Aguilera Educational Unit. For this purpose, this research has a quantitative approach through a non-experimental transactional study with correlational scope, with a sample of 155 high school students. On the other hand, the academic procrastination scale instrument (EPA) of Dr. Edmundo Arévalo Luna et al. was applied to evaluate procrastinating behavior. Barraza's systemic cognitive inventory (SISCO SV-21) was also used to measure students' academic stress. By means of the results obtained through Spearman's Rho statistic to relate the two variables of the research, therefore, a closely significant relationship was found with a value greater than 0.005 (Rho 0.995), that is, the more procrastination increases academic stress in students. For now, the levels of the two variables are low.